Faktor Penyimpangan Perilaku Homoseks (Suatu Kajian Tentang Penyimpangan Perilaku Homoseks di Desa Lam Sabang) - Sulaiman Sulaiman; Nuraini Nuraini (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
The focus of research is related to; (1) Factors causing irregularities homosexualbehavior in Lam Sabang village, (2) Psychological guidance to young victims of gayin Lam Sabang village, and (3) Policy for resolving the cases of gay in Lam Sabangvillage. While the subject of this study are five-public figures and one village’s leader. Theinstruments used were interview and observation. Data was analyzed by using descriptiveapproach. The findings of this study indicate: (1) The cause of gay’s behavior deviationin Lam Sabang village who causes to be sodomized teenagers in the village due to theperpetrators of sodomy had long divorced his wife and watch pornographic movies thatcan be accessed easily through handphone (HP), (2) Psychological guidance to youngvictims of gay in Lam Sabang village specifically not get service from professionals.However, efforts to strengthen the psychological only were given by the family to provideguidance and through lectures alone, and (3) The policy of resolving these gay cases atthe village level is not carried out because the case has been reported to the police andhas been prosecuted. So far, at the village level, there is no policy including customarysanctions also is not given to them.